Pattern-Based Evacuation Routing Planning for Urban Area - Acharya, Parishwar; Khadka, Shree Ram (Journal of Advanced College of Engineering and Management, 2016)
The rescue of affected people and their property in the urban areas during disaster has always been prominently important. The effective way of the evacuation has been important as well as interesting field of research for decades. The pattern-based evacuation (PBE) model restructures the traffic routing with the assumption of avoiding the crossing conflicts and minimizing the merging conflicts in the intersections. The problem has been formulated as a mix-integer programming problem. This paper focuses on the survey of the PBE model. Journal of Advanced College of Engineering and Management, Vol. 2, 2016, page:93-104